Prices, Liquidity, and the Information Content of Trades - Koski, Jennifer Lynch; Michaely, Roni (Review of Financial Studies, 2000)
We investigate the effect of asymmetric information on prices and liquidity by analyzing trades, quotes, spreads, and depths. Information content should increase with trade size and the information asymmetry of the trading period. Results show that price and liquidity effects are significantly associated with information content as measured by both trade size and timing relative to information events. Results are stronger for purchases than sales. Quoted prices are better measures of information effects than transaction prices, because they control for bid-ask bounce. Finally, trades that a priori contain no information have no impact on prices and liquidity, despite their large size.